Effect of the granular size on the zeolite content in the natural zeolite ores (Latakia University Journal -Basic Sciences Series, 2019)
Natural zeolite which named TS-14 from Tel- Asis area in Syria has beenstudied. The sample was crashed under fixed force, 5kg/cm2 and sieved with differentsizesieves. The product was divided to five samples with different size, andnamedTS-14-1,